IMMUNE SYSTEM DYSREGULATION IN ENDOMETRIOSIS: INFLAMMATORY PATHWAYS, IMMUNE CELL IMBALANCES, AND POTENTIAL THERAPEUTIC TARGETS - Takhirovna, Djurabekova Surayyo (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aims to investigate the immune system dysregulation in endometriosis, focusing on cytokine imbalances, immune cell malfunctions, and epigenetic modifications to identify potential diagnostic markers and individualized therapeutic options. Method: A total of 240 female participants, including 100 endometriosis patients and 50 healthy controls, were included in the study. Data were collected through cytokine measurements (IL-6, TNF-α, VEGF), immune cell profiling (Th1/Th2 dynamics, Treg/Th17 ratios, macrophage M1/M2 patterns), and epigenetic analysis (DNA methylation and microRNA expression) in blood and endometrial tissue samples. Results: Endometriosis patients exhibited significant immune imbalance with elevated levels of IL-6, TNF-α, and VEGF, disrupted Th17/Treg ratios, reduced NK cell activity, and an M2-dominant macrophage pattern, all contributing to chronic inflammation and tissue expansion. Novelty: The study highlights the role of epigenetic modifications and immune cell dysfunction in endometriosis, providing novel insights into its immunopathology. The findings support the development of precision medicine approaches targeting immune signaling pathways and biomarker-based therapies to improve treatment outcomes.